2013
DOI: 10.1186/1752-153x-7-158
|View full text |Cite
|
Sign up to set email alerts
|

Omani propolis: chemical profiling, antibacterial activity and new propolis plant sources

Abstract: BackgroundPropolis (bee glue) is a resinous honeybee product having a long history of application in many countries as a traditional remedy for treating wounds, burns, soar throat, stomach disorders, etc. It has been proved to possess beneficial biological effects, including antimicrobial, antioxidant, anti-inflammatory, cytotoxic, antiulcer, and many others. Bees gather propolis from diverse resinous plant parts and in different phytogeographic regions its chemical composition might vary significantly. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 39 publications
1
39
1
1
Order By: Relevance
“…The values of antimicrobial activities of this study for propolis extracts were higher than those found by Campos et al (2014), Miorin, Levy Junior, Custodio, Bretz, and Marcucci (2003) and Silva et al (2012), whose MIC were higher (0.59-3.65 mg/ml). In contrast, our antibacterial activities were lower than those described by Popova et al (2013) and Silici and Kutluca (2005), whose MIC ranged from 0.04 to 0.17 mg/ ml. These researchers studied antibacterial activities of propolis from different bees (Melipona orbignyi, Tetragonisca angustula, Apis mellifera caucasica) or from different floral origin (Populus spp., Salix spp., Eucalyptus spp., and Erica spp.)…”
Section: Discussioncontrasting
confidence: 82%
“…The values of antimicrobial activities of this study for propolis extracts were higher than those found by Campos et al (2014), Miorin, Levy Junior, Custodio, Bretz, and Marcucci (2003) and Silva et al (2012), whose MIC were higher (0.59-3.65 mg/ml). In contrast, our antibacterial activities were lower than those described by Popova et al (2013) and Silici and Kutluca (2005), whose MIC ranged from 0.04 to 0.17 mg/ ml. These researchers studied antibacterial activities of propolis from different bees (Melipona orbignyi, Tetragonisca angustula, Apis mellifera caucasica) or from different floral origin (Populus spp., Salix spp., Eucalyptus spp., and Erica spp.)…”
Section: Discussioncontrasting
confidence: 82%
“…Tetragonula bees gather propolis from diverse resinous plant parts, and in different phytogeographic regions, its chemical composition might vary significantly. 3 Curcumin, 8-epi-Helenalin, (-)-Sesamin, and Kushenol-F, were found in propolis extract have antioxidant activity. Curcumin, from genus Zingiberaceae, has a unique conjugated structure shows a typical radical trapping ability as a chain-breaking antioxidant, including two methoxylated phenols and an enol form of β-diketone.…”
Section: Discussionmentioning
confidence: 99%
“…3 The composition of propolis depends on diverse vegetation, phytogeographic region, and time of the collection. 4 Results from previous researchers found more than 300 components contained in propolis i.e.…”
mentioning
confidence: 99%
“…The vast majority of studies demonstrated that propolis reveals substantial properties, including the promotion of soft tissues healing and regeneration/reparation. Apart from its antibacterial [1][2][3][4][5][6], anti-inflammatory [7,8], antioxidant [9][10][11], immunoprotective [12], hepatoprotective activities [13,14], propolis has also anti-proliferative [15][16][17][18][19] and proapoptotic ones [20][21][22][23]. Composition of propolis is diverse and depends on both place of origin and time in which it has been collected.…”
mentioning
confidence: 99%